Numerical study of laminar core‐annular flow in a torus and in a 90° pipe bend. Issue 7 (31st March 2015) - Ooms, Gijs; Pourquie, Mathieu J. B. M.; Westerweel, Jerry
<x xml:space="preserve">Abstract</x> A numerical study has been made of laminar core‐annular through a torus. It is a follow‐up of the study by Picardo and Pushpavanam, AIChE J. 2013;59(12):4871–4886, who obtained an analytical solution for the case that the core is concentric and circular. In our study, we investigated the possibility of eccentric core‐annular flow and the deformation of the core‐annular interface. We found that a stable eccentric core position is possible, which is shifted in the direction of the inner or outer side of the torus depending on the balance of the normal stresses at the core‐annular interface. When these stresses are too far off from those for concentric and circular core‐annular flow, fouling of the wall occurs. We compared the results of core‐annular flow in a torus with those for a 90° pipe bend and found that the flow pattern in the torus is representative for the flow pattern in the bend. © 2015 American Institute of Chemical Engineers AIChE J, 61: 2319–2328, 2015